Simulation of Sports Training Action Optimization Model Based on IEC Algorithm - Huang, Pu (2023 International Conference on Telecommunications, Electronics and Informatics (ICTEI), 2023)
Sports can enhance our physical functions. In order to standardize sports actions and improve people's sports level, this article makes a quantitative research on the characteristics of sports training actions by using computer technology. In this article, based on IEC algorithm, a sports training action recognition model is constructed. This model is used to obtain the outline of sports action and realize the segmentation of sports action. Then, the characteristics of athletes' movements are extracted and analyzed, and the wrong movements are identified, so as to optimize the sports training movements. The experimental results show that the error of this model on the test set is low; At the same time, the classification accuracy of the model on the data set can reach 94.88%. Compared with the comparison model, the error and classification accuracy of this model are improved, and this result also verifies the reliability and superiority of this model. It is feasible to apply this model to sports training action recognition, and it can provide some technical support for sports training action recognition. Improve the effect and safety of physical training; It provides scientific basis and action examples for physical education teaching and scientific training.